Do local governments in Poland care about the physical activity of the local community? Health promotion activities targeting physical activity organized by local government units - Sobczyk, Karolina; Sas-Nowosielski, Krzysztof (Journal of Education, Health and Sport, 2023)
Introduction. When it comes to physical activity, activities at the local government level are extremely important, including, among other things, investing in the development of recreational and sports infrastructure in municipalities and counties, as well as implementing and financing health programs aimed at promoting physical activity among the population. Also, activities at the central level, implemented by the ministries of education, health, or transportation, aiming to implement policies that encourage the public to move, have a significant impact on the level of physical activity among young people. Objective. The study aimed to assess the prevalence of implementation of public health tasks by local government units in Poland, with a particular focus on activities in the area of physical activity. Material and methods. The study was conducted from May 13, 2020, to October 31, 2021. (18 months) in electronic form. The research group consisted of 1,118 representatives of local government offices of two levels: municipal (962 offices; 91.9% of the total) and district (91 offices; 8.1% of the total). According to the state at the time of the survey (as of 01.01.2021), Poland is divided into 16 provinces, 314 counties 2,477 municipalities (302 urban including 66 cities with county rights, 652 urban-rural and 1,523 rural). The survey covered 41.5% of municipalities and 29% of districts in Poland. Results and conclusions. The vast majority of local governments declare that they undertake activities in the area of physical activity, and these activities are often undertaken in cooperation with other local governments. Local governments very rarely implement health policy programs that include interventions in the area of physical activity, and among the reasons for not implementing such activities they usually point to financial and staffing problems.